FAKTOR-FAKTOR YANG MEMPENGARUHI PDRB (Produk Domestik Regiona Bruto) DI PROVINSI JAMBI - Nurhasanah Nurhasanah; Nurlia Fusfita; Nurfitri Martaliah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Economic growth is an indicator to evaluate the performance of an economy, especially to analyze the results of economic development achieved by a region. The economic growth measurement tool used at the regional level is GRDP. Gross Regional Domestic Product (GRDP) is the sum of gross value added from all economic sector activities that produce goods and services within a certain period of time in a region regardless of ownership of factors of production. This study aims to see how the partial and simultaneous influence of Islamic Bank financing, investment, and hotel taxes on GRDP in Jambi Province in 2013-2022. The method in this research is quantitative research with a time series data model. The analysis technique used is multiple linear regression analysis, hypothesis testing, and classical assumptions. The data used is secondary data sourced from the Central Bureau of Statistics and OJK. The results showed that partially Islamic Bank financing has a positive and significant effect on GRDP. Meanwhile, investment and hotel taxes have a positive and no significant effect on GRDP. Simultaneously Islamic Bank financing, investment, and hotel taxes have a positive and significant effect on GRDP in Jambi Province.